(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the clinical characteristics of HIV/AIDS infected pregnant women giving birth at Hanoi Obstetrics and Gynecology Hospital and their pregnancy outcomes. Subjects and methods: Retrospective cross-sectional study of 100 pregnant women diagnosed with HIV infection and giving birth at Hanoi Obstetrics and Gynecology Hospital from January 1, 2022 to December 31, 2023. Results: The average age of the participants was 32.44 ± 6.18 years old. Most pregnant women had one or more children, and none reported having an HIV-infected child. The majority of pregnant women ended their pregnancy by cesarean section, accounting for 87%. Among HIV-infected pregnant women undergoing cesarean section, 80.4% were performed for obstetric indications, with previous cesarean scars representing the most common reason (65.8%). In contrast, 13.8% of cesarean deliveries were indicated for the prevention of mother-to-child transmission (PMTCT). The use of PMTCT drugs significantly influenced the choice of delivery method, the difference was significant with p < 0.001. Regarding neonatal outcomes, most pregnancies were full-term (≥37 weeks), accounting for 89% of the cases. The majority of newborns weighed between 2500 g and 3500 g (90%), and 98% were HIV-negative. There was a statistically significant association between the newborns’ HIV status and both PMTCT drug use (p < 0.001) and mode of delivery (p = 0.008). Conclusion: The rate of HIV infection among newborns is 2%. The majority of HIV-infected pregnant women delivered by cesarean section, with previous surgical scars representing the most common indication. The combined use of PMTCT interventions and cesarean delivery was associated with a reduced risk of mother-to-child HIV transmission. Furthermore, PMTCT drug use had a significant influence on the choice of delivery method, suggesting that antiretroviral prophylaxis played an important role in clinical decision-making regarding mode of delivery.